PENDAMPINGAN INTERNET MARKETING DALAM MENDUKUNG KEGIATAN PROMOSI PADA UMKM JASMINE COLLECTION KEL. TANJUNG REJO KEC. SUKUN KOTA MALANG - Heru Utomo; Mohammad Maskan; Joko Samboro; Umi Khabibah; Titien Indrianti; Dwi Sudjanarti (Jurnal Pengabdian kepada Masyarakat, 2024)
competitiveness in order to survive, continue to run and even be able to develop. For this purpose, one strategy that can be done in managing their business is to apply internet-based information technology as a support in various processes of their business activities. Internet marketing is a marketing activity with the application of information technology, which includes activities to promote products and/or services through the internet. Jasmine Collection Kel. Tanjung Rejo, Sukun District, Malang City, one of the newly developing MSMEs, has not been optimal in implementing online marketing which is part of Internet marketing. Online marketing has been carried out through private Whatsapp and Instagram statuses. This PKM activity aims to help Jasmine Collection MSMEs maximize online marketing activities. The results of this activity are in the form of logos, ebooklets, ebrochures, and videos that will be uploaded to the MSME Instagram, and the website with the address https://jasminedaster2023.blogspot.com/